Dismissal of Acting Provincial Heads in Indonesia Based on the Transparency Principle Perspective - Anggraini, Novia Salfat; Affandi, Hernadi (Lex Journal: Kajian Hukum & Keadilan, 2024)
This study examines the legal regulation of the dismissal of acting regional heads in Indonesia, and how to apply the principle of transparency in the dismissal of acting regional heads. This study is normative research that uses qualitative methods and uses a case study approach. Permendagri Number 4 of 2023 concerning Acting Governors, Acting Regents, and Acting Mayors provides special guidelines regarding the appointment, duties, authority, and dismissal of acting regional heads. The Minister of Home Affairs regulates the term of office of the Acting Head of State for 1 (one) year and can be extended for the next 1 (one) year with the same or different person. The extension of the term of office of this acting officer cannot be extended if the results of the Minister's evaluation are followed. The dismissal of acting regional heads in Indonesia, if carried out without the principle of transparency, can cause various problems such as a lack of accountability and a decrease in public trust. To increase transparency, meaningful public participation is needed. The involvement of the Provincial DPRD is also a very crucial thing as a form of representation of the people. The government needs to regulate specific and detailed provisions related to the dismissal of acting regional heads in Indonesia.